Kazakhstan’s New Media Development: Role of Social Media on Society (Журналистика сериясы, 2016)
Kazakhstan has been independent for 25 years. In that time the media landscape dramatically changed, with traditional media (e.g., newspapers, television, radio) now supplemented by online media such as blogs, websites, social networks. Kazakhstan is a leader among the Central Asian countries and the Commonwealth of Independent States in the level of Internet capability. As an Emerging area of concern for developing countries such as Kazakhstan, new media research mainly includes two categories: the history of development of Internet and new media including social media in Kazakhstan, and the role of social media in Kazakh society. This article discusses research that explores the impact of new media, especially social media, on society.